2014
DOI: 10.1007/s10439-014-1142-1
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Rafts Direct Macrophage Motility in the Tissue Microenvironment

Abstract: Infiltrating leukocytes are exposed to a wide range of tissue elasticities. While we know the effects of substrate elasticity on acute inflammation via the study of neutrophil migration, we do not know its effects on leukocytes that direct chronic inflammatory events. Here, we studied morphology and motility of macrophages, the innate immune cells that orchestrate acute and chronic inflammation, on polyacrylamide hydrogels that mimicked a wide range of tissue elasticities. As expected, we found that macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…To determine the effect of substrate stiffness on the TLR4 signaling pathway, we first evaluated TLR4 expression in US and LPS–stimulated BMMs grown on collagen–PDL–functionalized 0.3 and 230 kPa gels. These two extreme stiffnesses were chosen because BMMs grown on these PA gels showed the most signficant differences in proinflammatory mediator concentrations and cell morphology remained homogenous on both 0.3 and 230 kPa gels [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…To determine the effect of substrate stiffness on the TLR4 signaling pathway, we first evaluated TLR4 expression in US and LPS–stimulated BMMs grown on collagen–PDL–functionalized 0.3 and 230 kPa gels. These two extreme stiffnesses were chosen because BMMs grown on these PA gels showed the most signficant differences in proinflammatory mediator concentrations and cell morphology remained homogenous on both 0.3 and 230 kPa gels [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…5,6,55,56) Furthermore, Michelle et al reported that macrophage single cell migration stimulated by lipopolysaccharide depends on ECM stiffness and disruption of the lipid rafts impairs stiffness dependency. 61) Taken together, these observations indicate that lipid rafts are required for ECM stiffness regulation of cell migration.…”
Section: Discussionmentioning
confidence: 74%
“…Lipid rafts are discrete cell-membrane structures enriched with cholesterol and glycosphingolipids where various signaling receptors, including syndecans [28] and integrins [29], accumulate and cross talk. Lipid rafts are typically found at the leading edge of migrating macrophages and have been implicated in cell adhesion, cytoskeleton organization, spreading, migration and extravasation [29,30]. We then wondered whether lipid rafts were necessary for SYN-NCs to spread onto Tat.…”
Section: Lymphocyte Adhesion and Spreading Onto Substrate-immobilized Tatmentioning
confidence: 99%